2008
DOI: 10.1177/0002716208322577
|View full text |Cite
|
Sign up to set email alerts
|

No Margin for Error: Educational and Occupational Achievement among Disadvantaged Children of Immigrants

Abstract: The authors review the literature on segmented assimilation and alternative theoretical models on the adaptation of the second generation, summarize the theoretical framework developed in the course of the Children of Immigrants Longitudinal Study, and present evidence from its third survey in South Florida bearing on alternative hypotheses. The majority of second-generation youth are progressing educationally and occupationally, but a significant minority is left behind. The latter group is not distributed ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
183
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(196 citation statements)
references
References 15 publications
9
183
0
4
Order By: Relevance
“…This supports the increasing awareness of the importance of studying the social context for ethnic minorities (Garcia Coll et al, 1996;Portes & Fernandez-Kelly, 2008). It also highlights the methodological needs to tease apart ecological, cultural, and immigration-related factors that are often undifferentiated in the existing studies on racial/ethnic minority groups.…”
Section: Exosystemsupporting
confidence: 59%
“…This supports the increasing awareness of the importance of studying the social context for ethnic minorities (Garcia Coll et al, 1996;Portes & Fernandez-Kelly, 2008). It also highlights the methodological needs to tease apart ecological, cultural, and immigration-related factors that are often undifferentiated in the existing studies on racial/ethnic minority groups.…”
Section: Exosystemsupporting
confidence: 59%
“…Many studies have shown that because of their need to build new lives in their receiving countries, immigrant families frequently see education as an investment in their children as individuals, as well as in the entire family (Portes & Fernandez-Kelly, 2008;Suárez Orozco, 1991). Immigrant parents often possess high levels of educational aspiration and have high expectations of their children.…”
Section: Do Turkish Families Muster More Family Support For Education?mentioning
confidence: 99%
“…Besides, recent research on intergenerational upward mobility among disadvantaged second-generation youths documents that parental involvement in children's upbringing and education might counterbalance the impact of disadvantaged origin. High parental ambitions, expectations, aspirations and specific types of parental support have been found to be the driving force for these successful achievements (Portes & Fernandez-Kelly, 2008;Schnell, Keskiner and Crul, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars can be interested in comparing children of immigrants of one or several national origins with children of natives in order, for instance, to measure ethnic inequalities, the effectiveness of anti-discriminatory policies, or the progress of integration using children of natives as a reference population (Bolzman et al 2003). Researchers may also be attentive to the differences between ways of incorporating the descendants of immigrants compared to the first generation of the same ethnic background in order to measure social mobility or social reproduction across generations (Portes and Fernandez-Kelly 2008;Bolzman et al 2003). Another important comparison concerns the similarities and differences between cohorts of children of immigrants with different ethnic and national backgrounds in order to test the presence of a "segmented assimilation" pattern in a particular society (Portes and Zhou 1993, Chap.…”
Section: Comparative Designsmentioning
confidence: 99%